Comparative anatomy of quadruped robots and animals: a review. (3rd July 2022) - Fukuhara, Akira; Gunji, Megu; Masuda, Yoichi
Abstract : Animals can instantly exhibit versatile behaviors in response to their circumstances to survive in harsh natural environments. For example, many animals chase prey, escape from predators, forage, utilize tools, build nests, and breed, in accordance with their niches with limited resources. To gain a deeper understanding of the source of this versatility in animals and apply the principles of their body plans to robotics, the authors, who work in the robotics and anatomy fields, jointly review and compare the essential body structure differences between quadruped robots and animals. This review provides a comprehensive discussion of the various functions of animal bodies by particularly focusing on the anatomical structure and gives examples of how these functions have been implemented in robotics. Conventional biomimetic robots have taken the approach of realizing animal functions as simple single-functional modules in order to achieve specific animal functions in the most efficient way. In contrast, animals have situation-dependent multi-functionality, in which one part of the body exhibits multiple capabilities depending on the situation. This new 'polysemantic body' design principle would transform the traditional processes for understanding and mimicking animals and make the interaction between biology and robotics more fruitful. GRAPHICAL ABSTRACT: UF0001